Evaluation of an Alternative Education Programme for Undocumented Children in Sabah: a Case Study - Rose Patsy Tibok (2019)
This study is an evaluative case study of the Alternative Education Programme (AEP) offered by an Alternative Learning Centre (ALC) in Sabah, Malaysia. Adopting a qualitative research approach based on the CIPP Model of Evaluation by Stufflebeam (1983), seven research questions were formulated to determine the context, input, implementation, and outcomes of the programme from the perspectives and narratives of the stakeholders in this ALC - the target group (community and parents), implementors (Head Teacher and teachers), and students (current and past). The semi-structured interviews with individuals and focus groups were analysed by way of the matrix method. This, together with findings from analysis of documents and class observations, generated insight into the context i.e. role and significance of the AEP and the ALC in the community and the level of support, importance and expectation placed upon the education provided. Findings on the input aspect pointed towards a lack of resources both physical (facilities and trained teachers) and financial (upkeep of ALC dependent on donations and sporadic funding). In terms of process, although there was congruency between the planning and implementation, several emergent issues were identified which ALC education were demonstrated through increased cognitive and affective skills, with these acquired knowledge utilised to secure jobs as teacher assistants, retail assistants, and in small private enterprises. The findings of the study raise implications on the depth and value of the education provided in the ALC in general. Among these are the need for (i) validation of the teaching and learning in the form of a more tangible or defined curriculum, (ii) alignment of learning content to those offered in government schools, (iii) extension of schooling beyond Year 6, (iv) trained and qualified teaching personnel, (v) involvement of stakeholders (corporations, government bodies and agencies) to alleviate funding challenges, and (vi) the eventual integration or inclusion of ALC learning as a form of acceptable pathway for further education and better job opportunities (Abstract by Author)